A simple technique adoption of hardware-in- the-loop process for multilevel inverter teaching at the undergraduate level / Shamsul Aizam Zulkifli and Go Hong Keng - Zulkifli, Shamsul Aizam; Go, Hong Keng (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
This project describes a single phase multilevel inverter simulation by using a Hardware-in-the-loop (HIL) technique with a low cost microcontroller. The interconnection between PC host (computer), Arduino (PWM and PI control) and Raspberry Pi (HIL interface) are the main parts in this project that creates the complete HIL process. Those microcontrollers are able to communicate with MATLAB SIMULINK in order to execute the functionality of the real time process in a closed loop control manner for the multilevel single phase inverter with voltage control technique. Real time simulations are executed for 7-levels inverter output by adjusting the reference signal of the voltage controller.